INKULTURASI SEBAGAI PROSES PEMBATINAN IMAN DAN NILAI-NILAI KRISTIANI - Alfons Segar (Jurnal Alternatif Wacana Ilmiah Interkultural, 2013)
This paper purpots to spell out the crucial challenges which emerge in the encounter beteen the local Christian communities and their traditional cultures:in other words, the interaction between the faith in Jesus Christ received from missionaries and ther salient features of the cultures which have shaped the people down the centuries.It aims, likewise, to outline the fruitful possibilities ofthe encounter.The basic assumptions ofthe concept of Inculturation are taken forgranted namelythat Inculturation neverto be conceived as a finished product, is essentially a process through which Faith in Jesus endures as the principle of inspiration and of action within a given culture. And that Inculturation of the Faith goes beyond the frontiers of Liturgy, spiritual-pastoral life and ecclesial organizations, and embraces the entire ambit of human life. Evangelization and Inculturation are positively correlated terms in an eminent degree.